Studi Deskriptif Korean Wave Terhadap Penguatan Ekonomi Kreatif Di Kota Serang - Yurista Bustomi; Aryanti Dwi Untari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to understand the development of the creative economy influenced by the Korean Wave in Serang City and to describe its impact on consumption patterns and production of local creative economy products. The research method used was qualitative with a descriptive approach. Data were collected through interviews, observation, and documentation. Data sources came from the Serang City Department of Tourism, Youth, and Sports (Disparpora), Korean-themed food businesses, and consumers. The results indicate that the Korean Wave has made a significant contribution to the development of the creative economy in Serang City, particularly in the culinary subsector. Entrepreneurs' creativity and innovation are evident in their ability to adapt authentic Korean dishes (such as tteokbokki, odeng, and kimbab) to local tastes and their use of social media as a promotional tool. In terms of consumption patterns, the Korean Wave has sparked public interest in trying culinary products featured in Korean dramas and on social media. In terms of production patterns, entrepreneurs employ flexible production strategies (constant, wave-like, and moderate) that are responsive to market demand and current viral trends. Furthermore, this phenomenon has also stimulated the local economic chain through the use of raw materials from local suppliers.